CONTRASTIVE ANALYSIS OF REFUSAL EXPRESSIONS IN JAPANESE AND BAHASA AT WORKPLACE - Gustini, Maria (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2018)
This article examines Contrastive Analysis of Refusal in Indonesian language and Japanese language. Up to now, there have been no contrastive researchs which compare refusal speech acts within Indonesian language and Japanese language, focused on working situations. This article reports on a study to investigate differences and similarities in the politeness strategies of refusals between Japanese language (JS) and Indonesian language (IS). This study employed politeness theory of Brown and Levinson (1987). Therefore the participants of this research were Indonesian and Japanese who currently work in company, school, etc. This research used descriptive method and collecting data using DCT (Discourse Completion Test) in Indonesian and Japanese. Therefore, the research subjects were those who already worked with the age-range from 22 to 50 years. 40 native speakers of Indonesian (IS) and 40 native speakers of Japanese (JS) participated in this study. All participants were asked to fill out a Discourse Completion Test (DCT) which written in the form role-play questionaire, consisting of 3 situations. DCT situations were categorized based on power and familiarity/social distance between speaker and hearer. Results are as follows: (1) JS and IS using apology, reason, fuka, and requeirment in refusal act. (2) IS explain reason clearly in refusal act. Other hand JS using aimai reason. (3) JS used expressions of apology appropriately according to their power (hierarchical position), while IS made appropriate use of these expressions according to relative social distance. (4) IS tend to using requeirement in each refusal act.